Myth and the Christian nation a social theory of religion - Mack, Burton L. (London ; Oakville, CT : Equinox Pub., 2008)
This is a book on a social theory of religion and culture. A survey of the meanings of the term religion from Columbus to Jonathan Z. Smith sets the pace. Examples are taken from ethnography, the ancient Near East, the Greco-Roman age, and Christendom in order to develop the concepts of "imagined world," "social formation," "mythic grammar," and "cultural mentality." What has been learned from the study of other peoples and their religions about the function of myths and rituals is then applied to an analysis of the Christian myth-ritual system and its social logic. The odd combinations of myt.
The religions of other peoples. Looking for religion in the new world ; Noticing the social interests in myths and rituals ; Watching myths in the making ; Thinking with myths about culture ; The religion of Christianity. Early Christian mythmaking ; The social formation of christendom ; The state of the Christian nation ; Religions in a polycultural world.
Includes bibliographical references (pages 276-283 and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Religion and sociology; Religion -- Social aspects; Christianity; Religion; Christianity; Religion and sociology; Religion -- Social aspects; Godsdiensten; Maatschappij; Christendom; Mythos; Religion; Ethnosoziologie; Christentum; Multikulturelle Gesellschaft; Soziologie; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; Electronic books